Evaluation of Cutting Transport Efficiency in KCl Polymer Drilling Mud with Poly Anionic Cellulose Low Viscosity (PAC LV) Additive - Maman Djumantara; Lisa Samura; Cahaya Rosyidan; Mulia Ginting; Mustamina Maulani; Andry Prima; Brilliani; Annisa Tri Aptanti (International Journal of Science and Environment (IJSE), 2026)
Effective transport of drilled cuttings out of the wellbore is a key requirement for maintaining drilling performance, since poor hole cleaning can trigger operational problems such as pipe sticking and inefficient circulation. This research examines how Poly Anionic Cellulose Low Viscosity (PAC LV) affects the cuttings-carrying performance of KCl Polymer water-based drilling mud. Two mud samples containing different PAC LV dosages were formulated and tested to obtain their density, plastic viscosity, yield point, gel strength, mud cake thickness, and filtration behavior. These rheological results were then applied to three engineering indicators, namely the Cutting Carrying Index (CCI), Cutting Transport Ratio (CTR), and Cutting Concentration in Annulus (CCA), to quantify cuttings transport performance. The findings show that raising the PAC LV dosage strengthens the mud's rheological profile, reflected in higher density, plastic viscosity, yield point, and gel strength, without compromising filtration quality. Both formulations produced CCI values above 1, CTR values exceeding 50%, and CCA values under 5%, confirming adequate cuttings-carrying capability and satisfactory hole-cleaning performance. Overall, the study confirms that PAC LV-treated KCl Polymer mud can deliver consistent rheological behavior and reliable cuttings removal under the tested conditions, contributing to safer and more efficient drilling operations.